1969
DOI: 10.1111/j.2044-8295.1969.tb01189.x
|View full text |Cite
|
Sign up to set email alerts
|

Signal Probability and Vigilance: A Reappraisal of the ‘Signal‐rate’ Effect

Abstract: Performance on a 40 min. visual task was studied as a function of signal probability. A separate group was tested at each of five levels of signal probability (0.02, 0.06, 0.18, 0.24 and 0.36). Percent detections increased with signal probability. This increase was accompanied by a rise in the false report rate, and analysis in terms of signal detection theory suggested that signal probability affects the subject's criterion (p) rather than his ability to discriminate (d').

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 6 publications
5
31
0
Order By: Relevance
“…It has been widely demonstrated that low signal probability reduces hit rates in classical low event-rate, low cognitive-load vigilance tasks by shifting criterion rather than by decreasing sensitivity (Baddeley & Colquhoun, 1969;Davies & Parasuraman, 1982;Parasuraman & Davies, 1976;Williges, 1973), and these effects are accompanied by a slowing of ''yes'' reaction times and speeding of ''no'' reaction times (Parasuraman & Davies, 1976), similar to the pattern we observe in visual search (Wolfe et al, 2005;Van Wert, Horowitz, & Wolfe, 2009). Thus, prevalence effects may be a more general phenomenon, applying across many cognitive domains.…”
Section: Introductionsupporting
confidence: 69%
“…It has been widely demonstrated that low signal probability reduces hit rates in classical low event-rate, low cognitive-load vigilance tasks by shifting criterion rather than by decreasing sensitivity (Baddeley & Colquhoun, 1969;Davies & Parasuraman, 1982;Parasuraman & Davies, 1976;Williges, 1973), and these effects are accompanied by a slowing of ''yes'' reaction times and speeding of ''no'' reaction times (Parasuraman & Davies, 1976), similar to the pattern we observe in visual search (Wolfe et al, 2005;Van Wert, Horowitz, & Wolfe, 2009). Thus, prevalence effects may be a more general phenomenon, applying across many cognitive domains.…”
Section: Introductionsupporting
confidence: 69%
“…Training screens contained a higher percentage of defects than experimental screens. Some researchers have found that higher defect rates lead to better signal detection (e.g., Baddeley & Colquhoun, 1969;Colquhoun, 1961;Fortune, 1979;Harris, 1968). In addition, participants received immediate feedback during training but did not receive feedback during the experimental session.…”
Section: Discussionmentioning
confidence: 98%
“…Do dramatic differences in target prevalence affect our ability to effectively search for that target? The vigilance literature suggests that the answer would be “yes; rare items are likely to be found less often” (Baddeley & Colquhoun, 1969; Colquhoun & Baddeley, 1967) but in those experiments, observers are looking for transient stimuli. In screening tasks, experts are examining complex images that remain present until they choose to move on to the next image.…”
Section: Reviewmentioning
confidence: 99%